1976
DOI: 10.1113/jphysiol.1976.sp011335
|View full text |Cite
|
Sign up to set email alerts
|

The cortical visual areas of the sheep.

Abstract: 1. A stereotaxic method for the sheep brain is described. 2. At its widest part the primary visual area (Visual I) of each hemisphere extends approximately 20 mm anteroposteriorly and, when unfolded, approximately 35 mm from side to side. It occupies both walls of the lateral sulcus, and extends medially to the medial wall of the hemisphere and to the depth of the ectolateral sulcus laterally. 3. The most lateral part of the primary visual area includes 10‐15 degrees of the ipsilateral field; the contralateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…However, we are not aware of any study of nasotemporal overlap in the marmoset. The representation of the ipsilateral field in V1 also exists in other mammals, where it tends to be larger than in primates (Clarke and Whitteridge, 1976;Volchan et al, 1988;Payne, 1990;Rosa et al, 1993). In the cat, Payne (1990) found evidence for both the callosal and the retinofugal pathways contributing to the ipsilateral representation in V1 and suggested that the two routes might operate synergistically.…”
Section: Ipsilateral Visual Field Representationmentioning
confidence: 88%
“…However, we are not aware of any study of nasotemporal overlap in the marmoset. The representation of the ipsilateral field in V1 also exists in other mammals, where it tends to be larger than in primates (Clarke and Whitteridge, 1976;Volchan et al, 1988;Payne, 1990;Rosa et al, 1993). In the cat, Payne (1990) found evidence for both the callosal and the retinofugal pathways contributing to the ipsilateral representation in V1 and suggested that the two routes might operate synergistically.…”
Section: Ipsilateral Visual Field Representationmentioning
confidence: 88%
“…In both these areas, cells with fields within 15-20°of the mid line tended to be excited by both eyes, and to be selective not only to monocular stimulus properties such as position in the field and orientation (Clarke & Whitteridge, 1976), but also to specifically binocular properties. The latter are the main concern of this paper, but it should be remembered that the monocular requirements had to be met in addition to the binocular ones for a cell to respond optimally, and, in fact, the cells in V2 were more sharply tuned to orientation than were those in VI.…”
Section: Comparison Of the Responses Of Cells In V1 And V2mentioning
confidence: 99%
“…The methods were the same as in the preceding paper (Clarke & Whitteridge, 1976), with a few additions described here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the visual streak is aligned to the horizon this retinal specialization allows the animal to view the whole horizon without the specialized eye movements required for scanning with an area or fovea centralis (Hughes, 1977). Indeed rabbits (Hughes, 1971), goats (Hughes & Whitteridge, 1973) and sheeps (Clarke & Whitteridge, 1976) also align the visual streak to the horizon to increase resolution and motion detection. In these species even a casual observation at their heads suggests that the visual field of these animals area unusually large (Hughes, 1977;Picanço Diniz, 1987).…”
Section: Asymmetric Representation Of the Contralateral Visual Field mentioning
confidence: 99%